Electrothermally responsive self-healing for carbon fiber/epoxy interphase based on Diels-Alder adducts. (26th May 2021) - Yang, Chongchong; Zhu, Dandan; Sun, Chengyuan; Chen, Buyun; Li, Yinghao; Pulidindi, Indra Neel; Zheng, Zhen; Wang, Xinling
Abstract: A more facile and more efficient self-healing strategy for carbon fiber/thermoset resin interphase was established based on electrothermal effect of carbon fiber (CF) driving the reversible transformation of covalent bonds. Diels-Alder cycloaddition adduct was introduced into the CF/epoxy (EP) interphase region to endow the interphase with thermoreversible covalent bonds through the oxidative co-polymerization and chemical surface grafting, which was nondestructive but more efficient. The modified carbon fiber was characterized via SEM, AFM, XPS and TGA. The CF/EP interphase temperature range in CF reinforced polymer composites (CFRPs) was adjusted through controlling the electric current applied to CFs according to the thermo-sensitivity of CF. The effect of electrothermal effect on the matrix resin around CFs was measured by micro-FTIR. The interfacial shear strength (IFSS) measurement verified that the electrothermal effect promoted the reversible transformation of the Diels-Alder cycloaddition adducts connecting the modified CFs with matrix resin, resulting in the self-healing behavior of the damaged interphase. This self-healing strategy not only can improve the interfacial adhesion of CFRPs without damages to the CF surface caused by the traditional oxidation modification methods, but also can reduce the possible heating aging and deformation of composites caused by convective thermal repairing methods. This strategy is a more efficient process. Graphical abstract: Image 1